TEKNIK PEMERIKSAAN COLON IN LOOP PEDIATRIK PADA KASUS OBSTRUKSI KRONIS DI INSTALASI RADIOLOGI RSUD KRATON PEKALONGAN - Retno Wati; Rintia Safitri; Sulistyono Sulistyono (Jurnal Kesehatan Tambusai, 2021)
Chronic intestinal obstruction is a blockage that occurs in the intestines, both the small intestine and the large intestine. Pediatric colon in loop is a radiological examination technique to determine the condition of the large intestine by inserting contrast medium retrograde in children. The pediatric colon in loop examination technique was performed usually using plain abdominal anteroposterior (AP) projection, contrast AP, lateral contrast, and post evacuation AP. Contrast media that are usually used are barium sulfate in adults and iodine in children. This study was conducted to find out how the pediatric colon in loop examination technique is carried out at the Radiology Installation of the Kraton Pekalongan Hospital so that it can help confirm the doctor's diagnosis of colon disorders. This research is qualitative research with a case study approach. The time of the study was carried out from November 11 to December 14, 2019. The results showed that the pediatric colon in loop examination in cases of chronic obstruction carried out at the Radiology Installation of the Kraton Pekalongan Hospital used three projections, namely plain AP, contrast AP, and lateral contrast. As for the contrast media using iodine mixed with NaCl in a ratio of 1:3. The pediatric colon in loop examination technique, in this case, was sufficient by using plain abdominal AP projection, contrast AP, and lateral contrast because it was able to establish the diagnosis. And contrast media uses iodine because it is water-soluble, so it is easily and quickly digested by the child's body.